Real-world comparison between weekly versus biweekly dosing of cetuximab for metastatic colorectal cancer - Himani Aggarwal; Yimei Han; Kristin M Sheffield; Zhanglin Lin Cui (Becaris Publishing Limited, 2023)
Aim: This real-world study aims to compare overall survival (OS) associated with biweekly (Q2W) versus weekly (Q1W) cetuximab dosing regimens for metastatic colorectal cancer (mCRC) treatment in the US. Methods: Adult patients with KRAS wild-type mCRC who received cetuximab ± chemotherapy from 2013 to 2019 were selected using Flatiron Health's electronic health records database. Propensity score matching was used to balance Q2W and Q1W cohorts on baseline patient characteristics. The Kaplan- Meier method was used for survival analyses. Several sensitivity analyses were conducted to assess the robustness of findings from the main analysis. Results: Of 1075 patients in the study, 60.7% received cetuximab Q1W and 39.3% Q2W. Median OS (95% confidence interval) in months was 17.2 (15.3, 18.8) for Q2W versus 14.3 (12.8, 16.0) for Q1W; p = 0.246. Similar OS between the dosing cohorts was observed in sensitivity analyses. Conclusion: Weekly and biweekly cetuximab had comparable effectiveness in this real-world study.